What the research says about concussion risk factors and prevention strategies for youth sports: A scoping review of six commonly played sports - Waltzman, Dana (J Safety Res, 2018)
INTRODUCTION: Given the growing research on potential adverse outcomes related to concussion and other serious brain injuries and the increased susceptibility for concussion among youth athletes, primary prevention is vital to protect the health and safety of this population. The purpose of this study is to summarize the current research on risk factors and primary concussion prevention strategies focused on specific youth sports, and to identify research gaps. METHODS: A literature search was conducted using six electronic databases. A scoping review method was used to identify studies that addressed risk factors or primary concussion prevention strategies focused on youth athletes (ages 5–18 years) in six sports (football, ice hockey, soccer, lacrosse, basketball, and wrestling). RESULTS: Of the 18 publications identified, the publications focused on risk factors (N = 11), policy (N = 1), rule changes (N = 3), education (N = 2), equipment (N = 2), and playing technique (N = 0). Some articles had information related to multiple topics. CONCLUSIONS: Current research on concussion prevention has primarily been focused on risk factors. There are a dearth of studies that examine primary concussion prevention in sports. When studies do exist, most focus on football and ice hockey. Only a small number of studies focus solely on risk factors or primary prevention in soccer, lacrosse, basketball, and wrestling—all sports in which concussions are common. PRACTICAL APPLICATIONS: This scoping review summarizes current research on concussion risk factors and primary prevention strategies in specific sports focused on youth athletes and identifies research gaps to help inform future efforts.